Ambivalent Fatherland: The Chinese National Salvation Movement in Malaya and Java, 1937–41 - Kankan Xie (Journal of Southeast Asian Studies, 2021)
China's resistance to Japanese aggression escalated into a full-scale war in 1937. The continuously deteriorating situation stimulated the rise of Chinese nationalism in the diaspora communities worldwide. The Japanese invasion of China, accompanied by the emergence of the National Salvation Movement (NSM) in Southeast Asia, provided the overseas Chinese with a rare opportunity to re-examine their ‘Chineseness’, as well as their relationships with the colonial states and the increasingly self-aware indigenous populations. This research problematises traditional approaches that tend to regard the NSM as primarily driven by Chinese patriotism. Juxtaposing Malaya and Java at the same historical moment, the article argues that the emergence of the NSM was more than just a natural result of the rising Chinese nationalism. Local politics and the shifting political orientations of overseas Chinese communities also profoundly shaped how the NSM played out in different colonial states.